2011
DOI: 10.1111/j.1570-7458.2011.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Host plant preferences of Hyalesthes obsoletus, the vector of the grapevine yellows disease ‘bois noir’, in Switzerland

Abstract: Bois noir is an important grapevine yellows disease in Europe that can cause serious economic losses in grapevine production. It is caused by stolbur phytoplasma strains of the taxonomic group 16Sr‐XII‐A. Hyalesthes obsoletus Signoret (Hemiptera: Cixiidae) is the most important vector of bois noir in Europe. This polyphagous planthopper is assumed to mainly use stinging nettle [Urtica dioica L. (Urticaceae)] and field bindweed [Convolvulus arvensis L. (Convolvulaceae)] as its host plants. For a better understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 24 publications
3
37
1
Order By: Relevance
“…In contrast to the nettle population studied by Kessler et al. (2011), the situation in Germany is such that field bindweed was the common host of H. obsoletus prior to the recent inclusion of stinging nettle. Thus, the two nettle-associations differ in their historical, genetic and resource backgrounds but produced similar adaptive implications for the trait survival.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the nettle population studied by Kessler et al. (2011), the situation in Germany is such that field bindweed was the common host of H. obsoletus prior to the recent inclusion of stinging nettle. Thus, the two nettle-associations differ in their historical, genetic and resource backgrounds but produced similar adaptive implications for the trait survival.…”
Section: Discussionmentioning
confidence: 99%
“…genetic diversity of 'Ca. P. solani' has been reported and generally related to complex interactions between the vector and the wide range of wild host plants (Kessler et al, 2011;Riolo et al, 2012). The phylogenetic analyses that were carried out for the vmp1, stamp, and secY genes were useful to study the relationships that the 'Ca.…”
Section: Populationmentioning
confidence: 99%
“…In recent years, rapid spreading of BN has been seen frequently, and this can be a limiting factor in several grapevine-growing regions (Maixner, 2011;Zahavi et al, 2013). BN spreading is influenced by the biology of the main vector, Hyalesthes obsoletus, together with other potential vectors (Imo et al, 2013;Landi et al, 2013;Cvrković et al, 2014), and their wide range of host plants (Kessler et al, 2011;Johannesen et al, 2012;Riolo et al, 2012;Cvrković et al, 2014). Disease management for BN is very difficult, as the phytoplasma and insect vectors are both not host specific, and thus their control is mainly based on agronomic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…For the BN nettle-type, the cultural control practices against U. dioica could be useful to reduce the disease (Maixner 2007;Kessler et al 2011) as showed by decreases of H. obsoletus population levels (Stark-Urnau and Kast 2008;Maixner et al 2010). In particular, the presence of U. dioica mostly in herbaceous vegetation surrounding the vineyard area and the edge effect in the spatial distribution of affected grapevines suggests controlling nettle in the ditches.…”
Section: Introductionmentioning
confidence: 98%